THE DEMAND AND SUPPLY FACTORS OF ECONOMIC GROWTH IN THE CZECH AND SLOVAK REPUBLIC - ĎURČOVÁ, Júlia; RAISOVÁ, Manuela (Journal of Advanced Studies in Finance, 2013)
The central European countries the Czech Republic and the Slovak Republic are referred to a group of the so-called Vysegrad countries (V4). Despite of the fact that the V4 countries are in its history, as well as geographically very close, their economic development is quite different. From this point of view it is interesting to study the similarity of the demand and supply factors influencing the economic growth in countries with different degree of European monetary integration. The aim of this paper is to compare the economic growth in the Czech and Slovak Republic. Two ways of economic growth calculation was used - demand perspective and supply perspective. Based on the analysis we conclude that the household consumption seems to have the most important influence on GDP variability. Based on the analysis of the supply point of view, we conclude that Slovakia and the Czech Republic have achieved its economic growth mainly by increasing the overall productivity of inputs.